Synthesis and properties of magnetic nanotheranostics coated with polyethylene glycol/5-fluorouracil/layered double hydroxide - Ebadi M (Dove Medical Press, 2019)
Mona Ebadi,1 Bullo Saifullah,1,2 Kalaivani Buskaran,2 Mohd Zobir Hussein,1 Sharida Fakurazi31Materials Synthesis and Characterization Laboratory, Institute of Advanced Technology (ITMA), Universiti Putra Malaysia, Serdang, Selangor 43400, Malaysia; 2Laboratory for Vaccine and Immunotherapeutic, Institute of Biosciences, Universiti Putra Malaysia, Serdang, Selangor 43400, Malaysia; 3Department of Human Anatomy, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, Serdang, Selangor 43400, MalaysiaCorrespondence: Mohd Zobir HusseinMaterials Synthesis and Characterization Laboratory, Institute of Advanced Technology (ITMA), Universiti Putra Malaysia, Serdang, Selangor 43400, MalaysiaTel +60 38 946 8092Email mzobir@upm.edu.myBackground: Cancer treatments are being continually developed. Increasingly more effective and better-targeted treatments are available. As treatment has developed, the outcomes have improved.Purpose: In this work, polyethylene glycol (PEG), layered double hydroxide (LDH) and 5-fluorouracil (5-FU) were used as a stabilizing agent, a carrier and an anticancer active agent, respectively.Characterization and methods: Magnetite nanoparticles (Fe3O4) coated with polyethylene glycol (PEG) and co-coated with 5-fluorouracil/Mg/Al- or Zn/Al-layered double hydroxide were synthesized by co-precipitation technique. Structural, magnetic properties, particle shape, particle size and drug loading percentage of the magnetic nanoparticles were investigated by XRD, TGA, FTIR, DLS, FESEM, TEM, VSM, UV-vis spectroscopy and HPLC techniques.Results: XRD, TGA and FTIR studies confirmed the formation of Fe3O4 phase and the presence of iron oxide nanoparticles, polyethylene glycol, LDH and the drug for all the synthesized samples. The size of the nanoparticles co-coated with Mg/Al-LDH is about 27 nm compared to 40 nm when they were co-coated with Zn/Al-LDH, with both showings near uniform spherical shape. The iron oxide nanoparticles retain their superparamagnetic property when they were coated with polyethylene glycol, polyethylene glycol co-coated with Mg/Al-LDH and polyethylene glycol co-coated with Zn/Al-LDH with magnetic saturation value of 56, 40 and 27 emu/g, respectively. The cytotoxicity study reveals that the anticancer nanodelivery system has better anticancer activity than the free drug, 5-FU against liver cancer HepG2 cells and at the same time, it was found to be less toxic to the normal fibroblast 3T3 cells.Conclusion: These are unique core-shell nanoparticles synthesized with the presence of multiple functionalities are hoped can be used as a multifunctional nanocarrier with the capability of targeted delivery using an external magnetic field and can also be exploited as hypothermia for cancer cells in addition to the chemotherapy property.Keywords: nano drug delivery, layered double hydroxide, core-shell nanoparticles, iron oxide nanoparticles, 5-fluorouracil